Phase II study of irinotecan with bolus and high dose infusional 5-FU and folinic acid (modified de Gramont) for first or second line treatment of advanced or metastatic colorectal cancer - Leonard, P (Nature Publishing Group, 2002)
We investigated the activity of irinotecan given with a more convenient modified bimonthly de Gramont regimen of bolus and infusional 5-fluorouracil [IrMdG] in advanced or metastatic colorectal cancer in the first and second line setting. Irinotecan 180 mg m(−2) was infused over 90 min. L-folinic acid 175 mg or d,l folinic acid 350 mg was given over 2 h followed by a bolus of 5-fluorouracil (400 mg m(−2)) and a 46 h continuous infusion of 5-fluorouracil (2.4–2.8 g m(−2)). Forty-six previously untreated patients (Group A) and 36 who had received 5-fluorouracil for metastatic disease (Group B) were recruited. Seventy-eight patients were evaluable for response. A partial response was seen in 13 out of 43 (30% [95%CI 28.1–31.9%]) in Group A and 8/35 (23% [95% CI 17.9–28.1%]) in Group B. 40% (95%CI 38.1–41.9%) of Group A and 26% (95% CI 20.9–31.1%) of Group B patients achieved disease stabilisation. The median progression free survival from the start of this treatment was 7 months (95% CI 4.4–9.6 months) in Group A and 5 months (95% CI 2.8–7.2 months) in Group B. Median overall survival was 14 months (95% CI 9.0–18.9) in Group A and 11 months (95% CI 5.9–16.1) in Group B. Grade 3–4 toxicity in both treatment groups were similar; leucopenia 17% and diarrhoea 7–8%. Grade 3–4 mucositis was not seen and severe alopecia affected only three patients. IrMdG is an active and well-tolerated regimen for both the first and second line treatment of advanced colorectal cancer. British Journal of Cancer (2002) 87, 1216–1220. doi:10.1038/sj.bjc.6600641 www.bjcancer.com © 2002 Cancer Research UK